IMPACT DE LA STRATÉGIE DE LUTTE CONTRE LES PIQÛRES ET LES ENVENIMATIONS SCORPIONIQUES SUR LES INDICATEURS DE SANTÉ DE LA RÉGION DE MARRAKECH TENSIFT EL HAOUZ (MAROC) - NekkaL Nesma; Soulaymani Bencheik Rachida; El Oufir Ghizlan; Rhalem Naima; Mokhtari Abdelrhani; Soulaymani Abdelmajid (European Scientific Journal, ESJ, 2014)
Morocco is one of the Mediterranean countries where the largest number of scorpion stings are recorded. The objective of this work is to evaluate the impact of the strategy against bites and scorpion envenomation in the region of Marrakech Tensift El Haouz, according to the monthly records established in 2001. The present work is a retrospective study of 84,237 cases of patients poisoned or bitten by a scorpion. The collection of information was carried out from January 2002 to December 2012. The collected data were analyzed according to several criteria to establish the evolution of indicators of morbidity and mortality in five provinces of the study area. The number of reported cases of bites from 2002 to 2012 is 84 237 cases and, and that of deaths is 332. Thus, an average incidence of 2.4 ± 0.3 per 1000 inhabitants, an average mortality of 0.009 ‰ ± 0.005, an average general lethality of 3.94‰ ± 1.76 and average specific lethality by envenomation of 32.61 ‰ ± 17.22. The average sex ratio was 0.92 in favor of the female with a highly significant difference ( x² = 168.92, P <0 The evolution of health indicators show a significant improvement in mortality and lethality, especially at the two provinces most affected by this disease.